(untitled) (International Journal of Economics Management and Social Science, 2026)
This study analysed the strategic management of educational institutions in the digital era to identify challenges and investigate prospects for improving educational quality. The primary objective was to provide direction to school administrators in developing programs that successfully address digital dynamics. This study combined qualitative methods with a literature review, utilising content analysis tools for data processing. The findings indicated that digital transformation presented both benefits and obstacles for educational institutions. Substantial hurdles included the necessity for infrastructure evaluation, continuous educator development, and regulatory amendments. Conversely, the digital era offered advantages such as gamification, interactive learning, analytics for tracking student achievement, and access to global resources. The study demonstrated that stakeholder engagement, adequate technical support, and adaptable techniques were essential to overcome these challenges. It was concluded that successfully addressing problems while leveraging opportunities facilitated optimal adaptation, hence enhancing educational outcomes and learning experiences.